Devosia rhizoryzae sp. nov., and Devosia oryziradicis sp. nov., novel plant growth promoting members of the genus Devosia, isolated from the rhizosphere of rice plants - Chhetri, Geeta; Kim, Inhyup; Kang, Minchung; Kim, Jiyoun; So, Yoonseop; Seo, Taegun (The journal of microbiology, 2022)
Two novel Gram-negative, aerobic, asporogenous, motile, rod-shaped, orange and white pigmented, designated as LEGU1 T and G19 T , were isolated from the roots of rice plants, collected from Goyang, South Korea. Phylogenetic analysis based on their 16S rRNA gene sequences revealed that they belonged to the genus Devosia and formed a different lineage and clusters with different members of the genus Devosia . These strains shared common chemotaxonomic features. In particular, they had Q-10 as the sole quinone, phosphatidylglycerol, diphosphatidylglycerol as the principal polar lipids and C 16:0 , C 18:1 ω7c 11-methyl and summed feature 8 (comprising C 18:1 ω 7 c /C 18:1 ω6c ) as the main fatty acids. The draft genome sequences of strains LEGU1 T and G19 T were 3,524,978 and 3,495,520 bp in size, respectively. Their average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) values were 72.8–81.9% and 18.7–25.1%, respectively, with each other and type strains of related species belonging to the genus Devosia , suggesting that these two strains represent novel species. The G + C content of strains LEGU1 T and G19 T were 62.1 and 63.8%, respectively. Of the two strains, only LEGU1 T produced carotenoid and flexirubin-type pigment. Both strains produced siderophore and indole acetic acid (IAA) in the presence of l -tryptophan. Siderophore biosynthesis genes, auxin responsive genes and tryptophan biosynthesis genes were present in their genomes. The present study aimed to determine the detailed taxonomic positions of the strains using the modern polyphasic approach. Based on the results of polyphasic analysis, these strains are suggested to be two novel bacterial species within the genus Devosia . The proposed names are D. rhizoryzae sp. nov., and Devosia oryziradicis sp. nov., respectively. The plant growth promoting effects of these strains suggest that they can be exploited to improve rice crop productivity. The type strain of D. rhizoryzae is LEGU1 T (KCTC 82712 T = NBRC 114485 T ) and D. oryziradicis is G19 T (KCTC 82688 T = NBRC 114842 T ).